PENINGKATAN MINAT BACA SISWA SDN MALEBER MELALUI PENGEMBANGAN SUDUT BACA DENGAN PENDEKATAN LINGKUNGAN LITERASI RAMAH ANAK - Tumundo, Celine Vandea A.; Fransisca Iriani R. Dewi; Fidiyah Anggini O. Nababan; Paula Jessica C. Sibi (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Tarumanagara, 2025)
The low interest in reading among children in Indonesia is a serious concern in human resource development. Based on UNESCO data, literacy in Indonesia is still relatively low, which is exacerbated by the dominance of gadget use from an early age. In this case, a team of Tarumanagara University students held a